Comparative analysis of super high-speed permanent magnet generator electromagnetic and temperature fields with the PWM and uncontrolled rectifiers. Issue 4 (1st October 2020) - Qiu, Hongbo; Zhao, Xifang; Wei, Yanqi; Tang, Bingxia; Yi, Ran; Cui, Guangzhao; Yang, Cunxiang
ABSTRACT: This paper presents a study on the influence of different rectifiers on a super-high-speed permanent magnet generator (SHSPMG), which is used in a micro-gas turbine distributed generation system. Taking a 117 kW, 60, 000 r/min SHSPMG as an example, the influence of PWM and uncontrolled rectifiers on the generator performances were studied comparatively. The current harmonics and its total harmonic distortion were analysed firstly, and the variation characteristics of voltage and current harmonics were obtained. Based on the 2-D electromagnetic analysis model, the losses of the generator with different rectifier load were studied, especially for the rotor losses, and the mechanisms of the losses variation were determined. By using the method of the 3-D coupling field between fluid and temperature, the temperature distributions of the SHSPMG connected with the PWM and uncontrolled rectifiers were calculated, respectively, and the influences of the different rectifiers on the generator temperature field were studied. It could be found that the PWM rectifier has the advantages of reducing generator losses and optimizing temperature distribution.